2006
DOI: 10.1128/cvi.13.5.556-560.2006
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Tissue Fibrosis Is Associated with Reduced Numbers of Naïve CD4 + T Cells in Human Immunodeficiency Virus Type 1 Infection

Abstract: The organized structure of lymphatic tissues (LTs) constitutes a microenvironment referred to as a niche that plays a critical role in immune system homeostasis by promoting cellular interactions and providing access to cytokines and growth factors on which cells are dependent for survival, proliferation, and differentiation. In chronic human immunodeficiency virus type 1 (HIV-1) infection, immune activation and inflammation result in collagen deposition and disruption of this LT niche. We have previously show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(133 citation statements)
references
References 27 publications
12
116
1
4
Order By: Relevance
“…Interestingly, FRC may also play a role in Ebola virus and HIV pathogenesis (31,32). Importantly, we demonstrate that the PD-1 inhibitory pathway greatly reduced stromal immunopa- thology and architectural disruption after infection.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, FRC may also play a role in Ebola virus and HIV pathogenesis (31,32). Importantly, we demonstrate that the PD-1 inhibitory pathway greatly reduced stromal immunopa- thology and architectural disruption after infection.…”
Section: Discussionmentioning
confidence: 65%
“…The hallmark of untreated immunodeficiency virus infections is the cumulative depletion of CD4 + T cells that is most marked in the later stages of infection by the predominant depletion in blood and LT of naive CD4 + T cells (3)(4)(5). This has been attributed to impaired output from the thymus (33-35) combined with loss in the periphery, in which T cells die by direct and indirect mechanisms related to chronic immune activation: (a) activated naive T cells become memory T cells that are susceptible to infection in which they succumb or are killed by virus-specific CD8 + T cells and (b) activated cells undergo activation-induced cell death (1,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there has also been increasing evidence that fibrosis induced by immune activation damages lymphoid tissue (LT) niches, thereby contributing to T cell depletion and impaired immune reconstitution upon institution of antiretroviral drug treatment (1,2). In HIV-1 infection, fibrosis, measured as collagen deposition in LTs, strongly correlates with depletion of naive CD4 + T cells and inversely correlates with the extent of immune reconstitution after suppression of viral replication by antiretroviral therapy (2)(3)(4)(5)(6). In pathogenic SIV infection as well, collagen deposition in the early stage of SIV infection of rhesus macaques (Macaca mulatta; RMs) is associated with initial decreases in CD4 + T cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that the initial immune activation and T cell proliferation were actually comparable between SMs and RMs in terms of CD25 and Ki67 expression, although the fraction of effector (i.e., granzyme B-positive) T cells was higher in RMs during both acute and chronic infection. Interestingly, the most striking difference between the two species was the rapid and substantial resolution of this state of immune activation in SMs but not in RMs, an event that appears to be sufficient to protect SMs from subsequent CD4 ϩ T cell depletion, chronic T cell apoptosis, and LT niche-damaging fibrosis, i.e., all phenomena that contribute to disease progression during pathogenic HIV and SIV infections (19,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%